(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness and safety of lower blepharoplasty combined with fat redistribution in the treatment of tear trough deformity. Subjects and Methods: A retrospective study was conducted on 114 patients who underwent lower blepharoplasty combined with fat redistribution for the treatment of tear trough deformity from July 4, 2016 to December 9, 2024. Medical records, pre- and postoperative photographs (at 6 and 12 months), complications, aesthetic outcomes, and patient satisfaction were analyzed. Results: The mean age of the patients was 49.37 ± 9.51 years. Females accounted for 77.19% of the cases. The rate of satisfied and very satisfied patients was 85.96% at both the 6-month and 12-month follow-ups. Good and very good aesthetic outcomes were observed in 85.96% of cases at 6 months and 88.6% at 12 months. Five patients (4.39%) developed postoperative chemosis, which completely resolved with conservative treatment. No severe complications or cases requiring reoperation were recorded. Conclusion: Lower blepharoplasty combined with fat redistribution is a safe and effective method for treating tear trough deformity, rejuvenating the lower eyelid area with a low complication rate.